2015
DOI: 10.1128/jvi.00422-15
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Yeast-Produced Enterovirus 71 and Enterovirus 71/Coxsackievirus A16 Chimeric Virus-Like Particles Provide the Structural Basis for Novel Vaccine Design against Hand-Foot-and-Mouth Disease

Abstract: Human enterovirus 71 (EV71) and coxsackievirus A16 (CVA16) are the two major causative agents for hand-foot-and-mouth disease (HFMD). Previously, we demonstrated that a virus-like particle (VLP) for EV71 produced from Saccharomyces cerevisiae is a potential vaccine candidate against EV71 infection, and an EV71/CVA16 chimeric VLP can elicit protective immune responses against both virus infections. Here, we presented the crystal structures of both VLPs, showing that both the linear and conformational neutraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
(42 reference statements)
1
26
1
Order By: Relevance
“…In this work, evidence is presented that EV71 VLPs of the C4 strain produced from the BEVS and purified through our multiple chromatography process retained key molecular and structural features for the first time, compared with those reported for native empty virions [24] and other EV71 VLPs [23, 35, 36]. The sedimentation coefficient of purified EV71 VLPs in this study (78S) was different from that of EV71 VLPs purified by CsCl (85S) as previously reported by Gong et al [23] using AUC analysis, and SDS-PAGE results showed that our EV71 VLPs consisted of VP0 (35 KDa), VP1 (33 KDa) and VP3 (26 KDa) capsid proteins were also different from EV71 VLPs consisted mostly of VP0 (35KDa), VP1(33 and 30KDa), VP3(27kDa), and a presumably incompletely processed band VP0-VP3(62kDa) purified by Gong et al As different strains, culture conditions, and storage conditions may influence on the final production[24, 35, 37], we speculate that these difference may be caused by our different production conditions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this work, evidence is presented that EV71 VLPs of the C4 strain produced from the BEVS and purified through our multiple chromatography process retained key molecular and structural features for the first time, compared with those reported for native empty virions [24] and other EV71 VLPs [23, 35, 36]. The sedimentation coefficient of purified EV71 VLPs in this study (78S) was different from that of EV71 VLPs purified by CsCl (85S) as previously reported by Gong et al [23] using AUC analysis, and SDS-PAGE results showed that our EV71 VLPs consisted of VP0 (35 KDa), VP1 (33 KDa) and VP3 (26 KDa) capsid proteins were also different from EV71 VLPs consisted mostly of VP0 (35KDa), VP1(33 and 30KDa), VP3(27kDa), and a presumably incompletely processed band VP0-VP3(62kDa) purified by Gong et al As different strains, culture conditions, and storage conditions may influence on the final production[24, 35, 37], we speculate that these difference may be caused by our different production conditions.…”
Section: Discussionmentioning
confidence: 86%
“…The sedimentation coefficient of purified EV71 VLPs in this study (78S) was different from that of EV71 VLPs purified by CsCl (85S) as previously reported by Gong et al [23] using AUC analysis, and SDS-PAGE results showed that our EV71 VLPs consisted of VP0 (35 KDa), VP1 (33 KDa) and VP3 (26 KDa) capsid proteins were also different from EV71 VLPs consisted mostly of VP0 (35KDa), VP1(33 and 30KDa), VP3(27kDa), and a presumably incompletely processed band VP0-VP3(62kDa) purified by Gong et al As different strains, culture conditions, and storage conditions may influence on the final production[24, 35, 37], we speculate that these difference may be caused by our different production conditions. Although they were both BEVS-produced, the purified EV71 VLPs in this study were shown to be mainly located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression of full-length P1 and 3CD genes of EV71 in recombinant systems resulted in the cleavage of P1 into full-length VP0, VP1, and VP3 subunits; together, they assemble into full-length VLPs (termed VLP full here) (18)(19)(20)(21). VLP full resembles the naturally occurring NEP in protein composition and overall structure (19,22). Although VLP full is highly immunogenic and protective in animal models (20,23,24), autocleavage of VP0 has been observed for unknown reasons in studies of EV71 (20,24) and the related virus coxsackievirus A16 (CVA16) (25,26).…”
mentioning
confidence: 99%
“…The radius of the CVA6 VLP is 161 Å ( Fig. 2A), which is similar to those of the expanded particles of EV71 and CVA16 (e.g., 159 Å for the EV71 procapsid, 161 Å for the EV71 VLP, and 162 Å for the CVA16 135S particle) and is slightly larger than those of the compact particles of EV71 and CVA16 (e.g., 155 Å for the EV71 mature virion, 156 Å for the CVA16 mature virion, and 156 Å for the CVA16 VLP) (23,(25)(26)(27), suggesting that the CVA6 VLP is likely in an expanded state. However, since no CVA6 mature virus structure is currently available, it is impossible to directly compare the radius of the CVA6 VLP with that of the CVA6 mature virion.…”
Section: Resultsmentioning
confidence: 68%